Relationship between Intensity of Parent-Child Interaction and Child Morale - Oktila Irvando; Syafruddin Wahid; Wirdatul Aini (Universitas Negeri Padang, 2019)
This research is a background by the bad moral of a child in Bungo Pasang Salido village in IV Jurai Pesisir Selatan district. Purpose this research is (1) to describe the interaction intensity of parents with a child, (2) to describe child morally, (3) to look relations between interactions intensity of parent-child with child morals. This research was quantitative correlational. The population in this research amounted to 67 with 34 people as a sample. Techniques of data collection with the questonanaire sheet statement. Data analysis techniques using percentage formulas and product-moment correlation formulas. The result showed (1) interactions intensity of parents with child still low, (2) child morals in Bungo Pasang Salido village, in IV Jurai Pesisir Selatan district was still bad, (3) there is a very significant correlation between interactions intensity of parent-child with child moral, because analysis value is 0,991 still confirmed with rtable for n=34 is 0,339 for significant level 5% more than for significant level 1% is 0,436.Keywords: Interaction Intensity, Child Moral